Reproductive Behaviour of Dalbergia sissoo (Shisham) - Tewari, Salil K., Shubhanjana; Pandey, S. B. S. (Indian Forester, 2002)
Present investigation deals with the reproductive biology of Dalbergia sissoo. Under natural conditions, pod setting of 11.09% (1998) and 17.19% (1999) were observed. In isolated single buds 1.71 percent (1998) and 7.97 percent (1999) pod setting were observed. In the year 1998, in isolated whole inflorescence, 186 pods were formed out of 6840 buds and in 1999, out of 4248 buds, only 144 pods were formed. In emasculated and bagged buds, 9 pods were formed out of 299 emasculated buds in 1998 and in the year 1999, only 14 pods were formed from 468 buds. No pod formation was observed in emasculated and left open buds indicate that a system of allogamous pollination is not working. Pod formation was also observed during hybridization (9.19 percent in 1998 and 6.94 percent in 1999) supports the idea that pod formation may take place if pollen even from other source is available.